Quick Sequential Organ Failure Assessment with Duration Stay for Intensive Care Patients - Prajgayatri, Galena Devi; Margo, Eveline (PT FORMOSA CENDEKIA GLOBAL, 2025)
An important metric for managing managing patients with serious illnesses is the duration of stay in the intensive care unit (ICU). According to data from Indonesia (2023), 68.2% among patients who were given treatment in the ICU for at least five days. Although research on this topic is still unclear, the quick Sequential Organ Failure Assessment (qSOFA) score is employed to forecast organ failure and the probability of prolonged duration stay. The aim of this study is to ascertain whether ICU patients' duration of stay and their qSOFA score are related. Getting secondary data from ICU patients admitted from the emergency room between January and December 2024, this observational study with a retrospective cohort design was carried out at Rumah Sakit Angkatan Laut Dr. Mintohardjo, Jakarta. 205 participants that met the inclusion criteria were chosen through successive sampling from all patients. For statistical analysis, the chi-square test was used with a significance level of p = 0.05. 50.2% of the individuals were between the ages of 18 and 59, and 54.1% of them were men, with an average stay of 4.84±3.46 days, the most prevalent qSOFA score was 2 (43.9%). The duration of stay in the ICU did not significantly correlate with the qSOFA score (p value = 0.326, p > 0.05).